Integrating Digital Tools Into Competency-based Elt Programs In Mali: Opportunities And Barriers - Koita Mahamadou Karamoko Kahiraba (The Journal of Studies in Language, Culture and Society, 2025)
This study investigates the integration of digital tools into competency-based English Language Teaching (ELT) programs in Mali, with the aim of identifying the opportunities and barriers associated with their use. It employs a mixed-methods approach, utilizing semi-structured interviews, surveys, focus groups, and classroom observations to gather perspectives. A total of 50 participants, including ELT teachers, students, and school administrators from urban and semi-urban areas, contribute to the data collection. The findings demonstrated two key results: first, while teachers recognize the potential of digital tools to enhance student engagement and learning outcomes, they face significant barriers, such as inadequate training, limited device access, and unreliable internet connectivity. Second, students express a strong interest in using digital tools, particularly multimedia resources, but encounter challenges related to high internet costs and unequal access to devices, exacerbating the digital divide. The study highlighted the need for targeted teacher training, infrastructure improvements, and policies promoting equitable access to technology to overcome these barriers. While substantial challenges remain, the integration of digital tools into Mali’s competency-based ELT programs offers significant opportunities for improving language-learning outcomes, provided that systemic issues are addressed.